1999
DOI: 10.1161/01.cir.99.9.1255
|View full text |Cite
|
Sign up to set email alerts
|

Regional Differences in the Recovery Course of Tachycardia-Induced Changes of Atrial Electrophysiological Properties

Abstract: The LA had a slower recovery of tachycardia-induced changes of atrial electrophysiological properties, and this might play a critical role in initiation of AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 26 publications
7
43
0
Order By: Relevance
“…The relative spatial distributions of atrial rate maladaptation and remodeling 4 may increase APD dispersion to facilitate the transition to and maintenance of AF. These spatially nonuniform repolarization dynamics may help to explain why repolarization sequence is less responsive to activation sequence in the atrium 9,11,24 than the ventricle. 25 Although we studied APD during Afl, the majority of prior studies have been made after electrical cardioversion from tachycardia, 8,15,17,24 meaning that those APDs were often measured at slower (nontachycardia) rates and may also have been influenced by the electrical shock.…”
Section: Nonuniformity and Rate Maladaptation Of Atrial Apdmentioning
confidence: 99%
“…The relative spatial distributions of atrial rate maladaptation and remodeling 4 may increase APD dispersion to facilitate the transition to and maintenance of AF. These spatially nonuniform repolarization dynamics may help to explain why repolarization sequence is less responsive to activation sequence in the atrium 9,11,24 than the ventricle. 25 Although we studied APD during Afl, the majority of prior studies have been made after electrical cardioversion from tachycardia, 8,15,17,24 meaning that those APDs were often measured at slower (nontachycardia) rates and may also have been influenced by the electrical shock.…”
Section: Nonuniformity and Rate Maladaptation Of Atrial Apdmentioning
confidence: 99%
“…Atrial electrical remodeling has been evaluated in several animal models of rapid atrial pacing, 1,2,4,7,9,10,[20][21][22][23] which have documented the shortening of the AERP and prolongation in atrial conduction time, but few have reported the inhomogeneity in the process of atrial electrical remodeling. We previously reported that the shortening of the AERP was larger at the RAA and LA sites than at the other atrial sites when the rapid pacing was performed from the RAA site for 2 weeks.…”
Section: Inhomogeneity Of Electrical Remodelingmentioning
confidence: 99%
“…Shortening of the atrial refractory period following establishment of atrial fibrillation and further lengthening after sinus rhythm restoration has already been demonstrated in humans as well as in animal models [2][3][4][5][10][11][12][13][23][24][25] . However, after long standing atrial fibrillation conversion to sinus rhythm, both lengthening and rate-adaptation of refractory period shows non-uniform time-dependent recovery in the atria, having been observed earlier on the right (hours) than References on the left atrium (days) thus, predisposing to dispersion of atrial refractoriness.…”
Section: (B) Mec (%) (C) Sec (%) (D) Met (Hz) (E) Set (Hz)mentioning
confidence: 91%
“…In animal models, the remodeling process has been demonstrated to be reversible after restoration of the sinus rhythm, and is characterized by progressive increase in both atrial conduction velocity and refractoriness (reversal remodeling) 1,2,10,11,13,22 . Recovery has also been demonstrated in human atria 3,[23][24][25][26] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation